Hubungan lama interaksi orang tua dengan penyimpangan perkembangan anak usia 1-3 tahun di kecamatan denpasar selatan: Relationship between duration of parents interaction and child development deviations aged 1-3 years in south denpasar district - Astawa, I Gede Satria; Wisnawa, I Nyoman Dharma; Susanto, Agus Donny (Stikes Wira Medika Bali, 2021)
Children’s future is determined by the children growth. Early detection of child development is carried out through careful monitoring of motor development, cognitive development and psychosocial development. Many factors can influence a child in carrying out his developmental tasks. This study aims to prove the duration of parents interaction as factors related to the possibility of deviation in the development of children aged 1-3 years in South Denpasar District. This study used a cross-sectional design. The technique for selecting the research location was done by multi-stage. The sample in this study was selected by using a saturated sample with 118 children in child care centers in South Denpasar District. Data collection was carried out by interviewing and filling out a questionnaire, using the development pre-screening questionnaire (KPSP). Data were analyzed by using chi-square test and logistic regression. There were 82.2% of children experienced appropriate development and 17.8% of children indicated that there was a possibility of developmental deviations. The results of bivariate and multivariate analysis showed that there were 3 variables that were significantly related to the possibility of deviations in child development, namely child care (AOR = 5,517; 95% CI: 1.13-26.84), length of interaction between parents (AOR = 4,160; 95% CI: 1.22-14.11), and the age of the child (A OR = 4.242; 95% CI: 1.47-12.18). Other variables such as gender, parents’ educational background, parents’ job and parents’ salary are not related to the possibility of deviations in child development. The duration of interaction and the child's age correlate to children developmental deviations. g of motor development, cognitive development and psychosocial development. Many factors can influence a child in carrying out his developmental tasks. This study aims to prove the duration of parents interaction as factors related to the possibility of deviation in the development of children aged 1-3 years in South Denpasar District. This study used a cross-sectional design. The technique for selecting the research location was done by multi-stage. The sample in this study was selected by using a saturated sample with 118 children in child care centers in South Denpasar District. Data collection was carried out by interviewing and filling out a questionnaire, using the development pre-screening questionnaire (KPSP). Data were analyzed by using chi-square test and logistic regression. There were 82.2% of children experienced appropriate development and 17.8% of children indicated that there was a possibility of developmental deviations. The results of bivariate and multivariate analysis showed that there were 3 variables that were significantly related to the possibility of deviations in child development, namely child care (AOR = 5,517; 95% CI: 1.13-26.84), length of interaction between parents (AOR = 4,160; 95% CI: 1.22-14.11), and the age of the child (A OR = 4.242; 95% CI: 1.47-12.18). Other variables such as gender, parents’ educational background, parents’ job and parents’ salary are not related to the possibility of deviations in child development. The duration of interaction and the child's age correlate to children developmental deviations.